A Case Report: Paranoid Schizophrenia With Stressing Point Screening For Paranoid Schizophrenia Prognosis - Andik Ferdiantoro; AS, Nur Azizah; Algristian, Hafid (UNUSA Press, 2021)
Background: Schizophrenia is a psychiatric disorder characterized by decrease or inability to communicate, reality disorders, namely hallucinations and delusions, cognitive impairment and difficulty to carry out daily activities. Paranoid schizophrenia is one of the most common types of schizophrenia and its has good prognosis among other types of schizophrenia. But the prognosis decision making for paranoid schizophrenia is influenced by the following factors: prepsychotic personality, acute or chronic, type of schizophrenia, age, administration of medication, presence or absence of precipitating factors, and heredity. Objective: This study aims to determine the prognosis of paranoid schizophrenia in case is using the factors above. The case study is based on the examination of patients in the outpatient psychiatric clinic of the Islamic Hospital of Jemursari Surabaya who have received the patient's consent. Methods: The method of diagnosis uses a pocket book for the diagnosis of mental disorders PPDGJ-III and DSM-V. Result: The results are showed that is paranoid schizophrenic patients with a poor prognosis (dubia ad malam). Conclusion: All of paranoid schizophrenia have not being a good prognosis (dubia ad bonam) because it is influeced by several factors, namely prepsychotic personality, acute or chronic, type of schizophrenia, age, administration of medication, presence or absence of trigger factors, and heredity. Keywords: Paranoid Schizophrenia, Prognosis of Paranoid Schizophrenia